PENERAPAN PRINSIP CHECK AND BALANCES DALAM SISTEM PEMERINTAHAN DI KABUPATEN KEPULAUAN SELAYAR PERSPEKTIF HUKUM ISLAM - Hidayat, Andi Dirga Ardana; Hamsir, Hamsir; HL, Rahmatiah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The purpose of this study is to find out the application of the principle of check and balances in executive and legislative relations in the Selayar Islands Regency Government in the perspective of Islamic law. This research is qualitative research with normative, sociological, and syar'i juridical approaches. The results of this study show that the application of the principle of check and balances between the executive and the legislature has been carried out in accordance with the provisions, it can be seen from the implementation of the supervisory function by the legislature to every policy planned and carried out by the executive, so that the stability of the government in Selayar Islands Regency is created. Although the principle of check and balances was not found to be applied in the time of the Prophet, but as long as the principle of mutual balance and mutual control between branches of power is intended to achieve benefit, then the application of the principle is not contrary to sharia.